Highly Efficient Near‐IR Photothermal Microneedles with Flame‐Made Plasmonic Nanoaggregates for Reduced Intradermal Nanoparticle Deposition. Issue 34 (10th October 2022) - Ziesmer, Jill; Sondén, Isabel; Thersleff, Thomas; Sotiriou, Georgios A.
Abstract: Near‐infrared (NIR) photothermal therapy by microneedles (MNs) exhibits high potential against skin diseases. However, high costs, photobleaching of organic agents, low long‐term stability, and potential nanotoxicity limit the clinical translation of photothermal MNs. Here, photothermal MNs are developed by utilizing Au nanoaggregates made by flame aerosol technology and incorporated in water‐insoluble polymer matrix to reduce intradermal nanoparticle (NP) deposition. The individual Au interparticle distance and plasmonic coupling within the nanoaggregates are controlled by the addition of a spacer during their synthesis rendering the Au nanoaggregates highly efficient NIR photothermal agents. In situ aerosol deposition of Au nanoaggregates on MN molds results in the fabrication of photothermal MNs with thin plasmonic layers. The photothermal performance of these MN arrays is compared to ones made by three methods utilizing NP dispersions, and it is found that similar temperatures are reached with 28‐fold lower Au mass due to reduced light scattering losses of the thin layers. Finally, all developed photothermal MN arrays here cause clinically relevant hyperthermia at benign laser intensities while reducing intradermal NP deposition 127‐fold compared to conventional MNs made with water‐soluble polymers. Such rational design of photothermal MNs requiring low laser intensities and minimal NP intradermal accumulation sets the basis for their safe clinical translation. Abstract : Photothermal microneedle arrays are developed utilizing plasmonic nanoparticles made by flame spray pyrolysis.